CORTIN PROTECTION AGAINST ANAPHYLACTIC SHOCK IN GUINEA PIGS - Wolfram, J. (The Rockefeller University Press, 1935)
Studies have been made on a possible protective action of cortin in the prevention of anaphylactic shock induced by crystallized egg albumin. Of sixteen control guinea pigs only two survived. Sixteen of thirty-three cortin-treated animals received hormone at the optimum period of from 2 to 6 hours before the shocking dose. Nine survived and two others showed some protection. In groups treated at other time intervals the evidence of protection is inconclusive. 2 weeks after the first test the cortin-treated survivors succumbed to a second antigen dose, which was not preceded by cortical extract.